Strengthening National Defense Policy through Total Defense Readiness against Non-Military Threats - May May Maysarah; Asep Adang Supriyadi; Reyhan Fakhreja; Khaerul Umam; Djoko Andreas Navalino (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study aims to develop and apply a three pillar analytical framework comprising institutional integration, technological innovation, and public participation to assess Indonesia’s Total Defense System (Sishankamrata) as a strategic response to non military threats. Employing a qualitative literature review of peer reviewed articles, policy documents, and official TNI communiqués from 2018–2025, the research systematically codes and refines themes across civil military coordination, technological readiness, and community engagement. Findings reveal that while Sishankamrata is formally embedded in national defense policy, its implementation is constrained by limited public awareness, fragmented inter agency mechanisms, and underdeveloped cyber capabilities. To bridge these gaps, the study recommends enacting clear legal frameworks for inter agency coordination, establishing integrated funding streams for joint task forces, expanding cyber resilience training for both military and civilian stakeholders, and launching nationwide public outreach campaigns to foster shared ownership of national defense. This adaptive, inclusive model equips policymakers and practitioners with actionable pathways to strengthen Indonesia’s resilience against cyberattacks, disinformation, pandemics, and economic disruption within a comprehensive Total Defense readiness paradigm.